Perancangan Media Interpretasi Wisata Budaya Dalam Rangka Meningkatkan Motivasi Pengalaman Berkunjung Wisatawan di Daya Tarik Galeri 16- Indonesian Bamboo Society - Nurul Rochmah Pramadika; Rusdin Tahir; Cecep Ucu Rakhman; Awaludin Nugraha; Tommy Andrianto (STIEPAR YAPARI Bandung, 2020)
This research aims to build a model of interpretation media design as an effort to improve the experience of visiting tourists with the appeal of cultural tourism. The design of interpretation media in this research, including; Interpretation board design, interpretation path design in three-dimensional (3D) form, slide show design in the gallery entrance area. Research location at Galeri 16 - Indonesian Bamboo Society, which was pioneered by Drs. Anang Sumarna Dipl.Tourism (Alm) 45 years ago. The interesting phenomenon in the presentation of a collection of displays that do not have the medium of interpretation as an information provider of a cultural tourism attraction. The results of documentary studies and interviews with visitors concluded that the experience of visiting Galeri 16 - Indonesian Bamboo Society had difficulty understanding information from each collection of displays, according to the context which in fact museums such as Galeri 16 - Indonesian Bamboo Society must be able to provide an interpretation of the function or meaning of collection objects. In other words, it is necessary to design several media interpretations as a facility for tourists in order to improve the tourist experience when traveling in the Galeri 16-IBS.